2003
DOI: 10.1038/sj.mp.4001354
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variations in CREB1 cosegregate with depressive disorders in women

Abstract: Major depressive disorder (MDD) constitutes a major public health problem worldwide and affects women twice as frequently as men. Previous linkage studies have identified a 451 kb region of 2q33-35 that exhibited significant evidence of linkage to Mood Disorders among women (but not men) from families with recurrent, early-onset MDD (RE-MDD), a severe and strongly familial subtype of MDD. This 451 kb region includes CREB1, an attractive susceptibility gene for MDD and related disorders. Sequence variations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 32 publications
7
78
1
1
Order By: Relevance
“…Other possible candidate genes include GPR55 (G protein-coupled receptor 55), which is expressed in human brain tissue and involved in extracellularintracellular signal transduction, and HDAC4 (histone deacetylase 4) which participates in epigenetic modification of core histones and. Work by Zubenko and colleagues has also suggested a role of CREB1 on mood disorders; this lies 20 cM centromeric to our linkage peak (Zubenko et al, 2003a). These authors have also identified a sex-specific association between the 124bp repeat allele of D2S944 and recurrent, early-onset major depression and with anxious depression in an independent U.S. and Dutch sample (Beem et al, 2006;Philibert et al, 2003;Zubenko et al, 2002).…”
Section: Discussionsupporting
confidence: 61%
“…Other possible candidate genes include GPR55 (G protein-coupled receptor 55), which is expressed in human brain tissue and involved in extracellularintracellular signal transduction, and HDAC4 (histone deacetylase 4) which participates in epigenetic modification of core histones and. Work by Zubenko and colleagues has also suggested a role of CREB1 on mood disorders; this lies 20 cM centromeric to our linkage peak (Zubenko et al, 2003a). These authors have also identified a sex-specific association between the 124bp repeat allele of D2S944 and recurrent, early-onset major depression and with anxious depression in an independent U.S. and Dutch sample (Beem et al, 2006;Philibert et al, 2003;Zubenko et al, 2002).…”
Section: Discussionsupporting
confidence: 61%
“…A female-specific association between BPAD and/or SCZ has been previously observed in both GPR50 15 and CREB1. 36 However, we cannot definitively say that there is no effect in males because the 95% CIs of the ORs in the male groups overlap with those of the ORs in the female samples where the significance was observed, indicating that there is no significant difference between their respective ORs. Alternatively, it is possible that the association detected in the females is a false-positive.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, we deemed it necessary to test the hypotheses that GPR78 may be involved in the pathogenesis of BPAD, SCZ or both BPAD and SCZ, in which all affected individuals were grouped together, as it has been previously suggested that the two psychiatric illnesses may share susceptibility loci. 33,34 Similarly, owing to evidence of differences between males and females in the manifestation of psychiatric illness 35 and from findings of sex-specific association in the analysis of other candidate genes, 15,36 analysis was also carried out on samples separated on the basis of gender.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Zubenko et al 3,11 are the first specific molecular genetic studies of early-onset and recurrent depression to be reported. The two studies of Zubenko et al upon which this commentary will focus are the most recent of a series of studies arising from this group's focus on early-onset recurrent illness.…”
Section: Searching For Genes For Early Onset and Recurrent Depres-sionmentioning
confidence: 99%
“…14 A model-free sex-dependent linkage analysis 15 of 2q33-35 (which contains D2S29944) reported that the highest multipoint LOD scores (between 6 and 7) were found in female affected relative pairs at D2S2321 and D2S2208, in a region containing CREB1-the gene for the cAMP-responsive element-binding protein (CREB). A subsequent linkage analysis of sequence variations in the CREB1 promoter and intron 8 11 reported that variants at these regions cosegregated with mood disorders in females in two of the 31 families that gave positive lod scores for this gene.…”
Section: Searching For Genes For Early Onset and Recurrent Depres-sionmentioning
confidence: 99%